OPTIMALISASI PELAKSANAAN INVESTASI ASET KRIPTO DALAM SEGI PERLINDUNGAN HUKUM INVESTOR - Daffa Khalisha Nabila (2023)
This study aims to analyze the legal protection of investors in Crypto Asset investment transactions. The presence of virtual currency in Indonesia as an electronic product has been a concern for the country since the beginning, but until now the government has not decided on steps, how to formulate written rules on movement and regulation, how to formulate policies. and investors or users securing transactions related to virtual investments are risky and vulnerable to cybercrime. This research method uses normative juridical with a statutory approach (Statute Approach) and a conceptual approach (Conseptual Approach). The results showed that the Implementation of Investment indicates the existence of Asymmetric Information between the Government, Bappebti, Physical Traders of Crypto Assets, and the Public. Socialization of the regulations issued by Bappebti is not carried out optimally or is not transparent so that many people do not know the entities registered with Bappebti. Bappebti as a regulator should educate the public about Crypto Assets and the importance of choosing investments through Crypto Asset traders registered and approved by Bappebti and issue policies regarding deadlines for the establishment of futures exchanges that facilitate the implementation of the physical Crypto Asset market to minimize the chances of fraud between Crypto Asset customers and Crypto Asset traders physical. Keywords: Legal Protection, Investment, Cryptocurrency.